Application of Picture as an Interactive Learning Media to Improve English Vocabulary in Elementary School - Jamal, Faisa; Maulina, Maulina; Faridawati, Faridawati; Nurdiansa, Eko Saputra (Journal of English Language and Education, 2025)
Vocabulary plays a pivotal role in English learning as it forms the foundation for developing core language skills. However, many elementary students struggle with vocabulary acquisition due to limited exposure and the use of less effective instructional methods. This research aimed to examine the effectiveness of picture media as an interactive learning tool in enhancing the vocabulary mastery of fifth-grade students at Kofalagadi Elementary School, Menui District. A pre-experimental method with a one-group pretest–posttest design was applied, involving 12 students as participants. The instrument used was a vocabulary test consisting of 20 items in the form of matching, multiple-choice, and jumbled-word questions. The findings showed that the students’ mean score improved from 65.83 in the pre-test to 95.00 in the post-test, with a mean difference of 29.17 points. The paired samples t-test indicated a significance value of 0.000 (p 0.05), confirming that there was a significant improvement in students’ vocabulary mastery after the intervention. These results suggest that picture media, when applied interactively, can serve as an effective instructional strategy to support vocabulary learning, particularly at the elementary school level. Furthermore, this study provides practical insights for teachers in selecting engaging media and demonstrates that picture-based strategies can be effectively integrated into classroom practice to foster student motivation and vocabulary development.